Celebrations : Living life to the fullest (General Conference of Seventh-Day Adventist Health Ministries Department, 2012)
By Fred Hardinge, DrPH, RD, FAND, Associate Director of Health Ministries for the General Conference of Seventh-day Adventists The Health Ministries Department has recently released a full-color, table-top book titled CELEBRATIONS. This book explores the secrets of a healthful lifestyle and an exuberant appreciation of the joy of living well. It has met with critical acclaim from those who have reviewed it.